Impactos socioambientais de grandes projetos urbanos na Amazônia: ecologia política e cartografia para gestão de recursos naturais na Bacia da Estrada Nova, Belém/PA - PANTOJA, Larissa Mourão (Universidade Federal do Pará, 2023)
This work sought the understand and identify the social and environmental impacts at Estrada Nova´s hydrographic basin trough the urban interventions of macrodenage in an area considered peripheral, swampy and facing sanitary issues. From on-site verification, the characterization of the area, the official documents available by PROMABEN and the open interviews with community leaders and municipal public managers, several socio-environmental impacts were identified. Among them, the top five were listed, based on technical descriptions and the principle of natural resource management. As the objective of this work is the spatial identification of impacts, mapping techniques were used based on theoretical references of political ecology, in order to understand how the territory reproduces socio-spatial segregation and affects the most vulnerable, starting from the conception of the capitalist system, especially in peripheral areas. The qualitative method was used based on interviews with community leaders, as they represent a portion of the local population. Due to the pandemic of the new coronavirus, the individual interview with the community became unfeasible. For mapping the impacts, it used GPS navigation and photographic records. The study area was concentrated around. Bernardo Sayão Avenue, as it was the area affected by the PROMABEN works. As a result of this research, five maps were generated, being a general map of the impacts and four divided by sub-basin, with the purpose of spatial identification of the socio-environmental impacts, and thus contributing to the autonomy of the population through the recognition of the territory and the acceptance of these impacts that occur in a way that contradicts the way of life of the population and the local reality.